2010
DOI: 10.1111/j.1582-4934.2010.01059.x
|View full text |Cite
|
Sign up to set email alerts
|

TELOCYTES – a case of serendipity: the winding way from Interstitial Cells of Cajal (ICC), via Interstitial Cajal‐Like Cells (ICLC) to TELOCYTES

Abstract: Ramon y Cajal discovered a particular cell type in the gut, which he named ‘interstitial neurons’ more that 100 years ago. In the early 1970s, electron microscopy/electron microscope (EM) studies showed that indeed a special interstitial cell type corresponding to the cells discovered by Cajal is localized in the gut muscle coat, but it became obvious that they were not neurons. Consequently, they were renamed ‘interstitial cells of Cajal’ (ICC) and considered to be pace-makers for gut motility. For the past 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

35
708
0
9

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 524 publications
(752 citation statements)
references
References 52 publications
35
708
0
9
Order By: Relevance
“…These cells were described in the prostate prior to the description of prostatic telocytes and to them were assigned the generic name of interstitial cajal‐like cells (ICLCs) 45. The characterization of telocytes was useful to avoid multiple ambiguous terminologies for CD34‐positive fibroblast‐like cells found in various organs, our data confirm the existence of fibroblast‐like CD34 and CD34/c‐Kit‐positive cells, consisting of prostatic telocytes, however, the data also point to the existence of fibroblast‐like cells c‐Kit positive and CD34 negative 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, to which the canonical definition of telocytes is not applied. Moreover, in structural terms we obtain some evidence of the existence fibroblast‐like cells that possess shorter and thicker cytoplasmic process at the periphery of the developing perialveolar smooth muscle, in which c‐Kit‐positive/CD34‐negative cells are verified.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…These cells were described in the prostate prior to the description of prostatic telocytes and to them were assigned the generic name of interstitial cajal‐like cells (ICLCs) 45. The characterization of telocytes was useful to avoid multiple ambiguous terminologies for CD34‐positive fibroblast‐like cells found in various organs, our data confirm the existence of fibroblast‐like CD34 and CD34/c‐Kit‐positive cells, consisting of prostatic telocytes, however, the data also point to the existence of fibroblast‐like cells c‐Kit positive and CD34 negative 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, to which the canonical definition of telocytes is not applied. Moreover, in structural terms we obtain some evidence of the existence fibroblast‐like cells that possess shorter and thicker cytoplasmic process at the periphery of the developing perialveolar smooth muscle, in which c‐Kit‐positive/CD34‐negative cells are verified.…”
Section: Discussionsupporting
confidence: 64%
“…In addition, our data point to the existence of fibroblast‐like cells in the prostate that are c‐Kit positive and CD34 negative, which escape the typical immunolabelling profile of telocytes (CD34 or CD34/c‐Kit positive) 9, 10, 11, 12, 13, 14, 15, 16, 17 And in the face of the immunolabelling profile of these factors during prostate development, in addition to some ultrastructural evidence, it is suggested that some telocytes (CD34 or CD34/c‐Kit positive) present at the periphery of the developing smooth muscle of alveoli could differentiate into c‐Kit‐positive and CD34‐negative fibroblast‐like cells that resemble ICCs. However, further studies will be needed to test this hypothesis.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Many investigations have documented that TCs and their Tps are resident in various organs of many mammals, including human, pig, gerbil, mouse, rat and degus 1, 2, 3, 4, 5. Studies on TCs and Tps have also been reported in lower animals, such as newts, zebrafish and turtles 6, 7.…”
mentioning
confidence: 99%
“…The main feature that distinguishes TCs from any other cells are their very long and thin prolongations, which are named telopodes (Tps) (1). The history of their development derives in a straight line from Interstitial Cajal Cells (ICC).…”
Section: Introductionmentioning
confidence: 99%